PENGAWASAN KECELAKAAN KERJA OLEH DINAS TENAGA KERJA PROVINSI SULAWESI UTARA (JURNAL ADMINISTRASI PUBLIK, 2022)
This research is motivated by the existence of critical thinking related to the problem of work accidentswhich are a threat to employers and workers, especially in the North Sulawesi area. The formulation of theresearch problem is How to Supervise Work Accidents by the Manpower Office of North Sulawesi Province.This study uses the supervisory management theory from Rusdiana and Ghazin (2014). This research is adescriptive research with a qualitative approach. The results of this study indicate that the supervision of theManpower Office of North Sulawesi Province is still lacking in socializing between the Service and theCompany because there are still companies and workers who are not concerned with safety while working sothat the number of accidents is still increasing from year to year. This conclusion is the Work AccidentSupervision carried out by the North Sulawesi Provincial Manpower Office to overcome work accidents.Suggestions for this research are (1) increasing the number of labor supervisory personnel, (2) supervisionrelated to the visit schedule must be optimized, (3) maximizing the field of labor supervision so that it iscarried out properly, (4) Further improving supervision efforts so that more optimal and effective.Keyword:Supervision,Accident,Labor